2011
DOI: 10.1007/s11524-010-9536-3
|View full text |Cite
|
Sign up to set email alerts
|

Urban–Rural Differences in Physical Activity in Belgian Adults and the Importance of Psychosocial Factors

Abstract: Recent research in urban planning and public health has drawn attention to the associations between urban form and physical activity in adults. Because little is known on the urban-rural differences in physical activity, the main aims of the present study were to examine differences in physical activity between urban and rural adults and to investigate the moderating effects of the physical environment on the relationship between psychosocial factors and physical activity. In Flanders, Belgium, five rural and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 36 publications
(62 reference statements)
6
46
1
1
Order By: Relevance
“…One of the crucial factors differentiating participation of children and adolescents in physical activities is their place of residence [20,13]. This was also reflected in the results of this study, according to which the percentage of both male and female adolescents who fulfilled the criteria of minimal and optimal physical efforts recommended for health was much larger in CzechowiceDziedzice than Katowice.…”
Section: Discussionsupporting
confidence: 61%
“…One of the crucial factors differentiating participation of children and adolescents in physical activities is their place of residence [20,13]. This was also reflected in the results of this study, according to which the percentage of both male and female adolescents who fulfilled the criteria of minimal and optimal physical efforts recommended for health was much larger in CzechowiceDziedzice than Katowice.…”
Section: Discussionsupporting
confidence: 61%
“…Esto puede deberse a que el Paraguay todavía es el país con mayor población rural de la región, y la condición rural es un determinante asociado con mayores niveles de AF cuando es estudiado en la región (12)(13)(14). En este sentido es importante hacer notar que en países con una dinámica demográfica diferente, en donde la migración del campo a la ciudad es más tardía, los entornos rurales son determinantes de menor cantidad de pasos diarios, de poco desplazamiento activo, y además es un condicionante de más obesidad que en el entorno urbano (15)(16)(17). La diferencia de los niveles de AF según sexo y grupos de edad está bien definida en diferentes estudios.…”
Section: Discusionunclassified
“…The conclusions from the 11 studies are inconsistent. Some (Cerin, Vandelanotte et al 2008, Van Dyck, Deforche et al 2009, Joh, Nguyen et al 2011, Van Dyck, Cardon et al 2011, Ding, Sallis et al 2012, Beenackers, Kamphuis et al 2013) support competitive mechanism while others (Rhodes, Brown et al 2006, Deforche, Van Dyck et al 2010, Carlson, Sallis et al 2012, Friederichs, Kremers et al 2013) support synergetic mechanism. Some studies found both mechanisms may exist; that is, the mechanism depends on the combination of the specific psychological and environmental characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(1) Populations. The examined populations ranged from adults in Australia (Cerin, Vandelanotte et al 2008), Belgium (Van Dyck, Deforche et al 2009, Van Dyck, Cardon et al 2011), Canada (Rhodes, Brown et al 2006), the Netherland (Beenackers, Kamphuis et al 2013, Friederichs, Kremers et al 2013, Beenackers, Kamphuis et al 2014), and the US (Joh, Nguyen et al 2011, Ding, Sallis et al 2012), Belgium youths (Deforche, Van Dyck et al 2010), and older adults in the US (Carlson, Sallis et al 2012). As we know, some European countries have much higher rates of walking and the social norm towards walking and private vehicles also differ considerably (Pucher, Buehler et al 2010, Buehler and Pucher 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation